2003
DOI: 10.1017/s0959269503001108
|View full text |Cite
|
Sign up to set email alerts
|

Emploi du ‘futur’ dans le français parlé des élèves d'immersion française

Abstract: ab st rac tNotreétude porte sur l'acquisition des variantes du futur par lesélèves d'immersion. Tous comme les locuteurs L1, cesélèves emploient trois variantes (le futur périphrastique; le futur fléchi et le présent de l'indicatif ) et ils le font au même niveau de fréquence: le futur périphrastique est de loin la plus fréquente. Nous discutons des facteurséducatifs et sociologiques auxquels on peut attribuer ces résultats inattendus. Ceci dit, lesélèves d'immersion expriment aussi parfois le futur avec des f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
2
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 18 publications
4
33
2
3
Order By: Relevance
“…In spite of such differences among the groups, reflecting an important effect for classroom instruction in the emergence of the inflected form, as well as for naturalistic exposure in bringing about use of the periphrastic form, it is also noteworthy that our learners do not reflect the findings for learners in a Canadian immersion context reported in Nadasdi et al (2003). While not reaching the native speaker level of 70% use reported by Poplack and Turpin, the periphrastic form constitutes the more dominant form in their learners' expression of futurity.…”
Section: Arborescences Revue D'études Françaises Issn: 1925-5357 112contrasting
confidence: 65%
See 3 more Smart Citations
“…In spite of such differences among the groups, reflecting an important effect for classroom instruction in the emergence of the inflected form, as well as for naturalistic exposure in bringing about use of the periphrastic form, it is also noteworthy that our learners do not reflect the findings for learners in a Canadian immersion context reported in Nadasdi et al (2003). While not reaching the native speaker level of 70% use reported by Poplack and Turpin, the periphrastic form constitutes the more dominant form in their learners' expression of futurity.…”
Section: Arborescences Revue D'études Françaises Issn: 1925-5357 112contrasting
confidence: 65%
“…In general, studies such as Bartning (1997), Harley (1992), Kihlstedt (1998), andLabeau (2005) have simply noted the limited use of the inflected future, such that it would seem to be acquired late, without revealing how acquisition of that specific form relates to other markers of futurity. Notable exceptions, however, are Ayoun (2013) and Nadasdi et al (2003). Ayoun's study focuses on North American university learners using data from a written composition and cloze test.…”
Section: The L2 Acquisition Of Futuritymentioning
confidence: 99%
See 2 more Smart Citations
“…The few studies that have examined how NNSs use and acquire future-time expression in French generally have taken English NSs as participants, be they in a secondary-school immersion setting in Canada (Nadasdi, Mougeon & Rehner 2003), in a university setting in an Anglophone country (Ayoun 2014;Howard 2012;Moses 2002), or living in the target language community (Gudmestad et al 2014). Regarding oral expression, Moses (2002) and Howard (2012), who were both working in a university setting, found that relatively advanced (end of university) students underuse the PF as compared to NSs in oral interview tasks.…”
Section: Expressing Future Time As a Nnsmentioning
confidence: 99%